The Influence of Firm Specific Determinants on Financial Performance in the Power Industry - J, Mafumbate; U, Ndlovu; A, Mafuka; P, Gavhure (Journal of Economics and Behavioral Studies, 2017)
This study concentrates on the impact of firm specific determinants on financial performance in the power industry. The firm specific determinants used in this study as independent variables were capital structure, firm size and liquidity whilst ROA, ROI and profitability were used as proxies of financial performance. Modigliani and Miller (1958) argue that capital structure has no impact on financial performance whilst the Trade-off theory suggests that the ideal capital structure that helps firm remain financially healthy is the trade-off between cost of leverage and the advantages of debt. Beyond that trade-off point, a firm will start making losses. The target population included 60 employees from all the 5 subsidiaries of the Holding company and researchers used 40 respondents as sample size to enhance reliability. A relationship was established between firm specific determinants and financial performance as measured by ROA, ROI and profitability. The results showed a negative but significant relationship between capital structure and financial performance and they support the pecking order theory which suggests that capital structure is a significant determinant of financial performance. Firm size and financial performance were also negatively related. However, a significant positive relationship was established between liquidity and financial performance. From the findings the researchers concluded that firm specific factors have a significant impact on financial performance. Researchers therefore recommend that ZESA holdings should use its internal funds such as retained earnings and more equity than debt when financing its activities so as to reduce leverage costs which lead to poor performance.